The Dissemination and Evaluation of Campus Ideological and Political Public Opinion Based on Internet of Things Monitoring. (14th June 2022) - Xu, Xiao; Sun, Bei
Abstract : With the advent of the information age, the rapid development of Internet of Things technology makes monitoring methods more flexible and changeable. As an intelligent application, the development of the Internet of Things brings convenience to public opinion monitoring. However, at present, due to the high price of transmission equipment, inconvenient maintenance, information delay, and other unfavorable conditions, real-time and controllable public opinion monitoring cannot be carried out on a large scale, and there are still many deficiencies in campus ideological and political public opinion monitoring. We found an effective transmission method, explored the network energy saving, dig deep into the transmission function of the signal system, and reduced the interference and mutual influence of various transmission accessories. In the application of the Internet of Things, the network public opinion is remotely monitored, the campus public opinion information is mastered, and its dissemination and development orientation are controlled. The exploration and research of online public opinion monitoring are in line with the goal of smart campus, and its theoretical development is constantly enriched.